Virtual music idol, the Chinese Leitkultur and the making of the world’s first virtual ‘Red Diva’ - Liuyan, Song; Wei, Chow Ow; Fan, Li; Gill, Sarjit S.; Linghan, Zhai (Canadian Center of Science and Education, 2024)
Luo Tianyi is currently the most popular virtual music idol in China, a product of the collective imagination of her fans. She has attracted many fans because of her cute image, her music works, and the space for imagination it brings to people. The development of virtual singers in China is deeply influenced by the Japanese ACGN (anime comic game novel) culture. At first, most of Luo Tianyi's fans were fans of the Japanese virtual singer Hatsune Miku or other anime fandoms with a strong subcultural nature. However, in recent years, Luo Tianyi has gradually attracted t he attention of the Chinese official media and gradually shifted from subculture to mainstream culture. As a result, it has not only had a significant impact on the Bilibili site, the largest interactive Internet platform for teenagers in China but also interacted with the official media, thus becoming an extraordinary music idol.